Effect Of Different Hydrocolloids And Cryoprotectants On Physicochemical Properties And Sensory Attributes Of Surimi Based Sausages - Santana, Palestina (2013)
The aim of this study was to determine effect of different hydrocolloids and cryoprotectants on physicochemical properties and sensory attributes of surimi based sausages. Sausages in first experiment were formulated using 100% frozen surimi (SP00), 50% frozen surimi and 50% surimi powder (SP50), and 100% surimi powder (SP100). The texture profile analysis (TPA) values (hardness, cohesiveness, springiness, and chewiness) and gel strength of SP100 were significantly lower (P < 0.05) than those of the SP00. Sensory analysis using a quantitative descriptive analysis (QDA) showed that hardness, cohesiveness, springiness, and chewiness scores of SP100 were lower than those of SP50 and the SP00. The effect of hydrocolloids (carboxymethylcellulose/CMC, guar gum, pectin, konjac, carrageenan, alginate, and fish gelatin) on surimi gel prepared from surimi powder showed CMC and alginate improved cohesiveness by 47% and 59%, respectively. Konjac improved cohesiveness, springiness, and chewiness by 3%, 15%, 89%, respectively. Overall, the potential hydrocolloid that improved the gel characteristics of surimi powder at level 0.5% were konjac, followed by CMC, and alginate. These three hydrocolloids then were used in sausage formulation. SAalg and SAkjc had higher gel strength (~26 and 28%, respectively) than SP100. SAkjc improved the WHC around 10% relative to SP100. SAcmc, SAalg, and SAkjc had higher QDA scores for springiness and cohesiveness than SP100.